2006
DOI: 10.22230/cjc.2006v31n2a1802
|View full text |Cite
|
Sign up to set email alerts
|

Convergence, Corporate Restructuring, and Canadian Online News, 2000-2003

Abstract: This paper critically examines the corporate restructurings that took place in the Canadian news industry in 2000, using findings from website analyses in 2001 and 2003 that assessed the impact of the changes on the provision of online news. The paper shows that despite their stated commitment to convergence, the restructured companies only selectively exploited the interactive potential of the Web, and that they tended to operate under traditional news and revenue strategies. It also documents a continued shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Forde and Wilson (2018) noted that the ability to provide a more nuanced critique in the realm of sports journalism requires a certain knowledge and skill set. Sports journalism is also constrained within the political economy of the sports media complex (Jhally, 2006; Sparks et al, 2006); therefore, journalists with the capacity and desire to produce work showing more complexities of identity, may have their agency severely compromised. The tensions that exist within the broad field of sports media compels researchers to also seek data from mainstream sources as well as ICTs that shed light, offer critiques, and create counter-narratives; yet, not all ICTs are created equal.…”
Section: Resultsmentioning
confidence: 99%
“…Forde and Wilson (2018) noted that the ability to provide a more nuanced critique in the realm of sports journalism requires a certain knowledge and skill set. Sports journalism is also constrained within the political economy of the sports media complex (Jhally, 2006; Sparks et al, 2006); therefore, journalists with the capacity and desire to produce work showing more complexities of identity, may have their agency severely compromised. The tensions that exist within the broad field of sports media compels researchers to also seek data from mainstream sources as well as ICTs that shed light, offer critiques, and create counter-narratives; yet, not all ICTs are created equal.…”
Section: Resultsmentioning
confidence: 99%
“…Due to fundamental differences between the two media, she concluded that there were no economies to be achieved and that the only special advantages of convergence were the cross-promotion of content across media and increased corporate size and influence (Doyle, 1999(Doyle, , 2002. Interviews with Canadian media executives found similar skepticism of the business advantages of convergence and also expressed concern over the increased conglomeration of Canadian news (Hildebrandt et al, 2005;Sparks et al, 2006). Part of the problem with convergence in Canada, as elsewhere, was that media companies had taken on high levels of debt in acquiring outlets in multiple media.…”
mentioning
confidence: 99%